2016
DOI: 10.1021/acs.inorgchem.6b00495
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Isomerism in Silver Acylpyrazolonato Complexes and Correlation with Their Antibacterial Activity

Abstract: Novel silver(I) acylpyrazolonato coordination polymers of formula [Ag(Q(R))]n (1-3) have been synthesized by interaction of silver nitrate with HQ(R) in methanol in the presence of an equivalent quantity of KOH (in general HQ(R) = 1-phenyl-3-methyl-4-RC(═O)-5-pyrazolone, in detail HQ(fb), R = -CF2CF2CF3; HQ(cy), R = -cyclo-C6H11; HQ(be), R = -C(H)═C(CH3)2). [Ag(Q(R))]n react with 2-ethylimidazole (2EtimH), 1-methylimidazole (Meim), and triphenylphosphine (PPh3), affording the mononuclear Ag(Q(fb))(EtimH) (4), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Silver compounds with anti-inflammatory ligands have recently been synthesized and their stability studied in the solid state with exposure to UV radiation. It has been found that the nature of the ligands, as well as the coordination number and geometry, can influence the stability in the context of exposure to light and temperature variations [ 5 , 7 , 10 , 11 ]. However, the stability of compounds in solution has not been widely studied, nor has the relationship between chemical properties and antibacterial activity over time.…”
Section: Introductionmentioning
confidence: 99%
“…Silver compounds with anti-inflammatory ligands have recently been synthesized and their stability studied in the solid state with exposure to UV radiation. It has been found that the nature of the ligands, as well as the coordination number and geometry, can influence the stability in the context of exposure to light and temperature variations [ 5 , 7 , 10 , 11 ]. However, the stability of compounds in solution has not been widely studied, nor has the relationship between chemical properties and antibacterial activity over time.…”
Section: Introductionmentioning
confidence: 99%
“…TEM imaging of bacteria exposed to silver nitrate showed phenomenon of DNA condensation, leading to the loss of its replication ability, along with deep structural damage of cell membranes [34]. Also, the antibacterial activity of silver may be due to its binding to the surface of the cell membrane disrupting the permeability and the respiration [69,70].…”
Section: Hirshfeld Surfaces Analyses Of [Ag (L1)] (No 3 ) and [Ag (L2mentioning
confidence: 99%
“…Silver-containing compounds continue to attract academic attention for their antimicrobial properties [1][2][3][4][5][6][7][8] but also for the immense variety of its coordination polymers, [9] and sometimes the two coincide [10]. A recent review is optimistic of the future role of silver in medicine, [11] while clinical studies are still not of sufficient quality to judge the practical usefulness of different silver based wound healing materials, the most common medical application [12].…”
Section: Introductionmentioning
confidence: 99%